Citizen participation in air pollution plans. An assessment without romance - Cordero Vega, Luis; Insunza Corvalán, Ximena (Revista de Derecho Ambiental, 2021)
This is an exploratory work that aims to analyze citizen participation as a mechanism to influence the definition of administrative acts or public policies. To this end, the process of development of Prevention and Decontamination Plans is examined, as instruments that manifest a global problem in a territory where the adoption of effective measures is essential and where the impact of participation should be conceptually influential and effective. As a result of the research, it is like to affirm that, the national regulatory framework, the process of drawing up the Plans and the results of participation are set out, demonstrating that there is no consistency between what is normatively intended with the implementation of participatory procedures.